Gastrointestinal nematode infection in beef cattle raised in silvopastoral and conventional systems in São Paulo state, Brazil - Oliveira, M. C.S.; Nicodemo, M. L.F.; Pezzopane, J. R.M.; Gusmão, M. R.; Chagas, A. C.S.; Giglioti, R. [UNESP]; Bilhassi, T. B. [UNESP]; Santana, C. H. [UNESP]; Gonçalves, T. C.; Rabelo, M. D.; Néo, T. A. (Springer Nature, 2017)
The use of silvopastoral systems (SPS) can be a good alternative to reduce the environmental impacts of livestock breeding in Brazil. Despite the advantages offered by public policies, many producers hesitate to use this system. One of the reasons is the lack of information on health and productivity of cattle raised under these conditions. The experiment reported here was designed to compare the behavior of infection by gastrointestinal nematodes and weight gain of beef cattle raised in a SPS and a conventional pasture system. We monitored the number of eggs per gram of feces, the prevalent nematode genus, data on climate, forage availability, weight gain and packed cell volume (PCV) of the animals bred in the two systems. The infection by nematodes was significantly higher in the cattle raised in the SPS (p < 0.05). The coprocultures revealed the presence of nematodes of the genera Haemonchus,Cooperia,Oesophagostomum and Trichostrongylus, in both systems, but the mean infestation rates of Haemonchus and Cooperia were higher in the SPS (p < 0.05). The average of PCV values did not differ between the cattle in the two systems. The individual weight gain and stocking rate in the period did not vary between the systems (p > 0.05). Despite the higher prevalence of nematodes in the SPS, no negative impact was detected on the animals’ weight gain and health. The results of this experiment indicate that under the conditions studied, there is no need to alter the parasite management to assure good productive performance of cattle.
Keywords: Cattle; Nematodes; Silvopastoral systems; Weight gain